Factors influencing the participation of Vietnamese enterprises in global value chains: Insights from the manufacturing and processing sectors - Vu, Huyen Thi Thanh; Nguyen, Hien Thi Thu; Vu, Hung Phuong; Lam, Do Van; Viet, Thao Tran (International Journal of Innovative Research and Scientific Studies, 2024)
This research aims to investigate the factors that impact the participation of companies in Vietnam's Manufacturing and Processing sector in the Global Value Chain (GVC). We employ panel data analysis with a dataset of 387,994 observations from 107,125 enterprises in this industry spanning 2011-2020. Both Ordinary Least Squares (OLS) and Generalized Moment Method (GMM) are used to assess the factors affecting the industry's GVC engagement. The Arellano-Bond test checks for autoregressive processes of order one (AR(1)) or order two (AR(2)) in the model to see if the idiosyncratic error term exhibits serial correlation. The Sargan test checks for over-identifying restrictions in the statistical model. The results reveal that the ratio of large enterprises" exerts the most significant positive influence on the participation of Vietnamese enterprises in the GVCs, closely followed by "Institutional and policy environment." Conversely, HHI, TFP, and GDP growth rates show significant negative impacts. For Foreign Direct Investment (FDI), horizontal spillovers are positive and statistically significant. However, significant results also show a negative coefficient in the Backward GVC and a positive one in the Forward GVC. From these findings, we point out some important policy implications: (1) the government should strengthen favorable conditions for the participation of large enterprises and leading SMEs; (2) It is necessary to improve the institutional and policy environment and refine policies to attract FDI, especially with a focus on promoting forward linkages to facilitate greater engagement of the enterprises in the GVCs.